Analysis of the Implementation of the Independent Curriculum Through the Understanding by Design (UbD) Approach in Chemistry Lessons : Literatur Review - Wibowo, Aldho; Aneu; Yulina, Indah Karina; Adwa, Nabilah (Education, Science, and Technology International Conference, 2025)
Understanding by Design (UbD) is a design or framework in learning that was first introduced by Grant Wiggins and Mc Ticghe. Understanding by Design (UbD) is defined as a learning design whose goal is to focus on achieving holistic student understanding. This study aims to review the implementation of the Independent Curriculum through the Understanding by Design (UbD) approach in Chemistry subjects through literature studies. The literature study was conducted by collecting data from various articles relevant to this topic, published in the period 2013-2025. This study concludes that the application of the Understanding by Design (UbD) model has proven to be effective and efficient in improving learning achievement, 21st century skills, and students' creative thinking skills, with fun, interactive learning, and encouraging independent learning.